UJI FITOKIMIA PADA DAUN KESUM (Polygonum minus Huds.) DARI KALIMANTAN BARAT - Dian Kartikasari; Ika Ristia Rahman; Abduh Ridha (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Kesum leaves are one of the plants that are widely available in West Kalimantan and are used by the community as vegetables or cooking spices. Research on the chemical content of kesum leaves has been carried out by several researchers, but research on whether there are differences in the chemical content obtained from the extraction with several types of solvents in kesum leaves has not been carried out. Therefore, in this study, the chemical content of kesum leaves will be tested. The method used is to test the presence of chemical compounds by phytochemical screening on several kesum leaf extracts using different solvents, namely 70% ethanol, 50% ethanol, 96% ethanol and methanol. The observations obtained were then analyzed descriptively and presented in tabular form. The results of the phytochemical screening test showed that the kesum leaf extracted in 70% ethanol, 50% ethanol, 96% ethanol, and methanol solvent contained phenols, flavonoids, saponins, and tannins. Moreover, extract of ethanol 70% and ethanol 50%, also contain terpenoids amd alkaloids, which were not detected on ethanol 96% and methanol extract.